Analisis persediaan bahan baku, reorder point dan safety stock pupuk urea pada PT. XYZ - Shofiyulloh, Muhammad Misbah; Sari, Rizqi Novita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the inventory of urea fertilizer raw materials at PT XYZ using the Economic Order Quantity (EOQ) method to determine optimal ordering, Reorder Point (ROP), and Safety Stock to minimize total inventory costs and reduce the risk of stock shortages. The data used includes raw material requirements, lead time, material prices, and storage costs. The results showed an average monthly requirement of 21,119 kg with a total cost of Rp3.23 billion. Ordering costs reached Rp335 million, while storage costs reached Rp386 million. With a Safety Stock of 2,645 kg and an ROP of 12,501 kg, the company can manage raw materials efficiently, ensuring smooth production without inventory buildup. Recommendations include implementing EOQ for cost efficiency and more optimized stock management.